Inadvertent arterial cannulation during intravenous cannulation of the cephalic vein - Thapa, Parineeta; Bhattarai, Balkrishna (Journal of Society of Anesthesiologists of Nepal, 2015)
No abstract available. -Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 37-38